Surgical issues in patients with breast cancer receiving neoadjuvant chemotherapy - King, Tari A.; Morrow, Monica (Nature reviews. Clinical oncology, 2015)
Key Points Neoadjuvant chemotherapy (NACT) does not prolong survival compared with adjuvant chemotherapy, but reduces the need for mastectomy and axillary lymph-node dissection, and thus surgical morbidity, without increasing the risk of locoregional recurrence Patients with high-grade oestrogen receptor (ER)-negative and/or HER2-positive breast cancers are more likely to experience pathological complete response to NACT than those with low-grade, ER-positive tumours Lumpectomy, following NACT, does not need to remove the entire volume of breast tissue initially occupied by the tumour Sentinel lymph-node biopsy (SLNB) after NACT accurately stages the axilla and is associated with a low rate of nodal recurrence in patients presenting with clinically negative axillary lymph nodes In patients who convert to clinically node-negative disease, SLNB after NACT has a false-negative rate of <10% only when ≥3 sentinel nodes are identified; nodal recurrence rates after SLNB alone in this population are unknown The relative contribution of pre-NACT and post-NACT stage (degree of pathological response) to local control is uncertain; tailoring local therapy based on response to NACT is being evaluated in ongoing trials Although neoadjuvant chemotherapy (NACT) does not prolong survival compared with adjuvant chemotherapy, this approach does not increase the risk of locoregional recurrence, and the high rates of response following NACT have had a considerable impact on locoregional treatment considerations. In particular, NACT can decrease the need for mastectomy and axillary lymph-node dissection. This Review discusses issues relating to the identification of ideal candidates for NACT, and also those surrounding surgery of the breast and axilla in women with breast cancer who receive NACT. Early randomized trials of the addition of neoadjuvant chemotherapy (NACT) to the treatment regimen of patients with breast cancer failed to demonstrate an improvement in overall survival compared with conventional adjuvant therapy; nevertheless, the increased opportunities for breast conservation, owing to downstaging of the primary tumour, and enthusiasm regarding the potential to tailor systemic therapy based on responses observed in the neoadjuvant setting, resulted in the adoption of this approach as a useful clinical tool. That the effectiveness of NACT varies by molecular subtype is becoming increasingly clear, and although the potential of tailoring adjuvant systemic therapy based on treatment response before surgery remains to be realized, the increasing rates of pathological complete response following NACT have had a considerable impact on locoregional treatment considerations. For example, NACT reduces the need for mastectomy and axillary lymph-node dissection, thus decreasing the morbidity of surgery, without compromising outcomes. However, selection of the ideal candidates for preoperative chemotherapy remains critical, and personalizing local therapy based on the degree of response is the subject of ongoing clinical trials. This article reviews the current issues surrounding surgery of the breast and axilla in patients with breast cancer receiving NACT.